2016
DOI: 10.1186/s13071-016-1504-7
|View full text |Cite
|
Sign up to set email alerts
|

Tick-borne pathogens of zoonotic and veterinary importance in Nigerian cattle

Abstract: BackgroundTicks and tick-borne diseases undermine cattle fitness and productivity in the whole of sub-Saharan Africa, including Nigeria. In this West African country, cattle are challenged by numerous tick species, especially during the wet season. Consequently, several TBDs are known to be endemic in Nigerian cattle, including anaplasmosis, babesiosis, cowdriosis and theilerioris (by Theileria mutans and Theileria velifera). To date, all investigations on cattle TBDs in Nigeria have been based on cytological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
74
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(103 citation statements)
references
References 54 publications
7
74
4
Order By: Relevance
“…Our result is similar to previous reports from southern Italy (39.2%) (Carelli et al., ). Our result is in contrast to findings from other countries where the prevalence of A. centrale was much lower for example in Tunisia (15.1%) (Belkahia et al., ), Nigeria (6.3%) (Lorusso et al., ), southern Italy (13.8%) (Ceci et al., ) and Turkey (0.8% and 18%) (Aktas & Ozubek, ; Aktas et al., ).…”
Section: Discussioncontrasting
confidence: 98%
See 1 more Smart Citation
“…Our result is similar to previous reports from southern Italy (39.2%) (Carelli et al., ). Our result is in contrast to findings from other countries where the prevalence of A. centrale was much lower for example in Tunisia (15.1%) (Belkahia et al., ), Nigeria (6.3%) (Lorusso et al., ), southern Italy (13.8%) (Ceci et al., ) and Turkey (0.8% and 18%) (Aktas & Ozubek, ; Aktas et al., ).…”
Section: Discussioncontrasting
confidence: 98%
“…As this species is naturally attenuated (Rar & Golovljova, ), it is used as a live vaccine in Australia, Africa and South America (Bock, de Vos, Kingston, & Carter, ). A. centrale was identified in cattle from Tunisia (Belkahia et al., ), Italy (Ceci et al., ; Zobba et al., ), Turkey (Aktas et al., ) and Nigeria (Lorusso et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…The initial touch-down cycles were used to increase the specificity of the PCR reactions. All PCR products were used in the RLB assay as described previously [25] and were visualized using the ChemiDoc Touch Imaging System (Bio-Rad). The RLB membrane was exposed for 10 min to detect the chemiluminescence of the bound PCR products.…”
Section: Methodsmentioning
confidence: 99%
“…This species is considered to have low pathogenicity in cattle, thus having little economic importance (Bell-Sakyi et al 2004). Kubelová et al (2012) reported the presence of this pathogen in 14% of bovines in Angola and Lorusso et al (2016) found this pathogen in 52.4% of bovines in Nigeria. According to Wernecke et al (1979) and Capinera (2008), A. variegatum, A. hebraeum , and A. lepidum are vectors of T. velifera in South Africa and possibly also in Mozambique.…”
Section: Discussionmentioning
confidence: 97%